The Techniques of decorating - McCloud, Kevin (Dorling Kindersley, 1995)
This decorating guide explains techniques ranging from craquelure to marbling, colourwashing to liming wood, and provides information on tools and materials. The step-by-step photographs show exactly what to do, while the life-size details show the effect being aimed for.